2016
DOI: 10.1038/leu.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

JAK-STAT and G-protein-coupled receptor signaling pathways are frequently altered in epitheliotropic intestinal T-cell lymphoma

Abstract: Epitheliotropic intestinal T-cell lymphoma (EITL, also known as type II enteropathy-associated T-cell lymphoma) is an aggressive intestinal disease with poor prognosis and its molecular alterations have not been comprehensively characterized. We aimed to identify actionable easy-to-screen alterations that would allow better diagnostics and/or treatment of this deadly disease. By performing whole-exome sequencing of four EITL tumor-normal pairs, followed by amplicon deep sequencing of 42 tumor samples, frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 52 publications
8
101
0
Order By: Relevance
“…Similar to the Nairismagi study, 6 we confirm the presence of a high incidence of JAK/STAT pathway mutations in EATL II (76% and 80%, respectively). In contrast to the 24% prevalence of GNAI2 mutations in that report, we did not identify any GNAI2 mutations in our 20 cases; rather we found a high percentage of RAS/RAF pathway mutations (31.6%), previously not reported in EATL II.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Similar to the Nairismagi study, 6 we confirm the presence of a high incidence of JAK/STAT pathway mutations in EATL II (76% and 80%, respectively). In contrast to the 24% prevalence of GNAI2 mutations in that report, we did not identify any GNAI2 mutations in our 20 cases; rather we found a high percentage of RAS/RAF pathway mutations (31.6%), previously not reported in EATL II.…”
supporting
confidence: 89%
“…Until recently there were few genetic/genomic studies of these lymphomas, with the exceptions of a study of NK/T and γδ T-cell lymphomas that included cases of γδ EATL II 5 , and a second more comprehensive study of EATL II. 6 Both groups reported a high incidence of STAT5B mutations in EATL II, while the second group also identified frequent mutations of JAK3 and the α G-protein subunit GNAI2, as well as some less common mutations. To further understand the molecular pathogenesis of these rare lymphomas, we analyzed our own series of primary ITCL, which included EATL I, EATL II, and PTCL-NOS, by targeted next generation sequencing (NGS) of genes associated with T-cell neoplasia and proliferation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1 T-LGL leukemia have also been seen in various T-cell neoplasms, including gd hepatosplenic T-cell lymphoma, 13 T-cell acute lymphoblastic leukemia, 14,15 T-cell prolymphocytic leukemia, 16 type II enteropathy-associated T-cell lymphoma, 17 and extranodal NK/T-cell lymphoma, 18 suggesting that these are shared with other T-cell malignancies. The analyses of STAT5 target genes with chromatin immunoprecipitation sequencing have shown that STAT5B is a key factor in T-cell development, binding to molecules such as DOCK8, SNX9, FOXP3, and IL2RA.…”
mentioning
confidence: 99%
“…MEITL is not associated with celiac disease (CD) that mainly occurs in Europe and it is distributed all over the world with predominance in Asia. Although it is well‐known that copy number gain of 9q34 is frequently found in MEITL in both of Asian and Western countries, the genetic alterations and mutational landscape of MEITL has been recently described, and MEITL is characterized by activating mutations of the JAK‐STAT pathway with mutations of STAT5B being the most common (reportedly as high as 63%) with other commonly mutated genes being JAK3 , GNAI2 , CREPBP and SETD2 . MEITL histologically shows a monomorphic proliferation of the lymphoma cells and immunohistochemically is positive for CD8, CD56 and megakaryocyte‐associated tyrosine kinase (MATK); the expression of TCRβ and TCRγ was variable among the cases.…”
Section: Clinical Findings Tumor Size Immunohistochemistry Pcr Cgmentioning
confidence: 99%